Business Feasibility of Luxe Nails & Style in Lippo Cikarang: Opportunities and Challenges in the Fashion and Nail Art Industry - Monica, Febri Intan; Yonanda, Tifanny; Pradhani, Nafitria Endhika; Jamila, Aliya; Romadon, Rizqi (Lentera Ilmu Nusantara, 2025)
The purpose of this article is to discuss the Bangkok fashion and nail art business from Luxe Nails & Style located in Lippo Cikarang Mall, Bekasi Regency. The data collection method is an interview method by interviewing the business owner, supported by observations to capture consumer preferences and business practices more comprehensively. The purpose of this study is to determine how the marketing mix of Bangkok fashion and nail art Luxe Nails & Style, with a particular focus on its contribution to the literature on creative industry business feasibility and the significance of marketing strategy for sustaining competitiveness. The research method used is a descriptive research method with a qualitative approach. The results of the study show that Bangkok fashion and nail art from Luxe Nails & Style are always updated with trend models, which demonstrates the business’s adaptability to dynamic consumer demands in the fashion and beauty sector. Prices are quite affordable for all groups, Place or distribution is easily accessible to consumers, promotion uses promotional strategies to the public directly and indirectly, and these findings reinforce the feasibility of the business when assessed through the marketing mix dimensions. In conclusion, Bangkok fashion and nail art Luxe Nails & Style can be said to be growing rapidly by using marketing strategies with marketing mix techniques, namely by continuing to produce unique and attractive fashion and nail art, appropriate and competitive product prices, promotions using direct techniques to consumers and utilizing social media to support wider customers, and strategic distribution locations make it easier for customers to find the store, while contributing practically by offering insights for entrepreneurs in similar industries and theoretically by enriching discussions on feasibility studies of creative businesses in emerging markets.